Teen Titans. Starfire - Garcia, Kami (DC graphic novels for kids., 2024)
When Kori Anderson, who has a connective tissue disorder, and her popular older sister, Kira, participate in a pharmaceutical company's clinical trial, she begins to discover strange powers and hopes to discover the truth about these abilities--and her sister's boyfriend.